The Benefits and Limits of Guanxi in US–China Research Collaborations - Chen, Morris; Haupt, John; Hu, Die; Wen, Wen; Lee, Jenny (International Higher Education, 2023)
Social networks based on Chinese culture, or guanxi, played an important role in scientists’ capacity to produce knowledge, their collaboration experiences, and in navigating the securitized research environment targeting collaboration between the United States and China.